The immune and metabolic treatment approach of using testosterone on mice models of liver injury - Amer, Johnny; Salhab, Ahmad; Snobar, Hadeel; Alhabil, Yazan (Frontiers in Pharmacology, 2023)
Background: Natural killer (NK) cells showed an anti-fibrotic effect; however, their function is thought to be impaired in advanced liver injury. In the current study, we aimed to assess the immune and metabolic impact of testosterone on mice model of liver injury. Methods: Carbon-tetrachloride (i.p injected) of acute (2 weeks) and chronic (4 weeks) models of male mice (n=108) of liver injury was performed. Testosterone (4 mg/kg mouse body weight) was injected i.p following the first week of acute model of CCl4 and following the second week of the chronic model of CCl4. At the end of experiments, mice were sacrificed, and serum were collected for assessing liver enzymes of ALT, AST, inflammatory marker of IL-6, metabolic makers of C-peptide levels as well as for lipid and glucose profiles. Livers were harvested and used for histological assessments for inflammation and for fibrosis. Fibrosis profile from liver extracts; aSMA and Collagen III, were assessed by RT-PCR. Moreover, liver tissue-resident NK cells were isolated and evaluated for their activity through assessing INF-g and IL-6 receptor by the ELISA and flow-cytometry respectively. Results: Serum ALT, AST, IL-6, and metabolic assessments of cholesterol, triglyceride, C-peptide, fasting blood sugar, and fibrotic profiles were linearly correlated with disease progressions. Histological characterization of the liver was worsened in the chronic model of liver injury. Testosterone-treated mice exhibit a significant reduction in collagen depositions with less dense fibrosis tissue associated with reduced liver injury enzymes and metabolic markers in both the acute and the chronic CCl4 mice model in favor of the later one (P<0.05). Moreover, testosterone treatments displayed significant decrease in serum IL-6 of 2.4-fold (p=0.0001) and 2.3-fold (p=0.0003) in the acute and chronic models, respectively (p=0.002) and data were associated with increase in INF-g release from NK associated with a reduction in their IL-6 receptor expressions (P<0.05). Conclusion: Our results showed effects of testosterone on mediating a decreased expressions of NK IL-6 receptors and consequently induced their activation, results that in part could explain the amelioration in liver injury findings. Our results suggest an anti-inflammatory and anti-fibrotic treatment approach of testosterone for delaying disease progressions.